Application Of Computer Vision Systems For Passenger Counting In Public Transport - Lengvenis, P.; Simutis, R.; Vaitkus, V.; Maskeliunas, R. (Elektronika ir Elektrotechnika, 2013)
This paper presents a passengers counting system based on computer vision. System prototype were created and installed in Kaunas public city transport. Four algorithms were created to calculate passengers on public transport and their advantages and disadvantages were analyzed. Qualitative detection algorithms analysis carried out. Promising results were obtained with the Algorithm of barrier simulation for zones (ABSZ) which has low false rate and it is effective for people-counting. Counting results information can be used for public transport optimization or service quality improvement. DOI: http://dx.doi.org/10.5755/j01.eee.19.3.1232